Physical and Mechanical Properties of Zirconia Toughened Alumina (ZTA) Composites Fabricated by Powder Injection Moulding - Nutthita Chuankrerkkul (Science Faculty of Chiang Mai University, 2019)
Zirconia toughened alumina (ZTA) ceramic composites have been fabricated by powder injection moulding. The ZTA composites, having alumina with zirconia in range of 0-15 wt %, were mixed with polymeric binder to form feedstocks. The binder composed of polyethylene glycol (PEG), polyvinyl butyral (PVB), and stearic acid (SA). The plunger-typed injection moulding machine was employed in this work. The moulded specimens were subjected to PEG removal using water immersion method. The remaining PVB was eliminated during ramping up to the sintering temperatures. Pressureless sintering was done at temperature of 1600, 1650, 1700 and 1750 °C with a holding time of 2 hour. Physical and mechanical properties, i.e. density, hardness and flexural strength were evaluated. Microstructures of sintered components were characterized using scanning electron microscope. The results showed that sintering temperature strongly affected the physical and mechanical properties of the composites. The amount of zirconia also played an important role in the hardness and strength values of the specimens. Microstructures revealed that zirconia inhibited grain growth of alumina, consequently, enhanced properties of ZTA. The densities of ZTA ceramic composites obtained in this work were 97-98% of the theoretical value when sintered at 1650-1700 °C.